Redução de aplicações de inseticidas através da adoção de táticas de manejo integrado do Triozoida limbata (Enderlein, 1918) (Hemiptera: triozidae) em goiabeira - Pazini, Wilson Carlos [UNESP]; Galli, Julio Cesar [UNESP] (Soc Brasileira Fruticultura, 2011)
The guava tree pest that has been requesting larger control frequency, in the area of Jaboticabal - São Paulo in the last years, is the psilideo Triozoida limbata. Thus, the objectives of this research were: a) Compare control tactics T. limbata based on monitoring and selectivity of insecticide to decrease the applications; b) To register and to correlate the natural enemies in habitants in guava tree ecosystem with the key pest and with meteorological factors; c) See if the control of T. limbata affects the population of fruit flies and d) To verify the efficiency of appropriate insecticides to IMP, in control of T. limbata. The experiment was conducted in 2004, in an orchard of Paluma cultivar in Vista Alegre do Alto, SP. The used strategies were (doses in g.a.i./100L water): control; imidacloprid + beta-cyfluthrin (2.5 + 0.3); acetamiprid (4.0); fenpropathrin (15.0) and regional conventional treatment. It was concluding that is possible to reduce the number of applications of less aggressive insecticides to the environment and the man, with the adoption of monitoring of T. limbata and implementing the action level. The natural enemies' populations densities (Scymnus spp., Cycloneda sanguinea, Azia luteipes, Crysoperla spp., Polybia spp., Brachygastra ssp.) present positive correlations with the populations of T. limbata. Population fluctuations of T. limbata and natural enemies are not altered by meteorological factors (precipitation and temperature) in irrigated orchard. The population of Anastrepha spp. is minimized when of the applications is for control T. limbata. The insecticides imidacloprid, imidacloprid + beta-cyfluthrin, acetamiprid and fenpropathrin are efficient in the control of T. limbata.
Reduction of insecticides applications through the adoption of integrated management tactics of triozoida limbata (enderlein, 1918) (Hemiptera: triozidae) in guava tree
Keywords: Insecta; Coccinelidae; Triozidae; traps; Psidium guajava